Tax control analysis as part of tax management to determine the efficiency of VAT payments at PT CTA - Diah Rizkyan Dewi (ARKA INSTITUTE, 2022)
Tax control analysis is carried out to determine or measure the efficiency of paying taxes. This study was carried out on the payment of value-added tax (VAT). This research was conducted at PT. CTA, which is a company engaged in trading computer spare parts. The research aims to determine or measure the efficiency level of VAT management, which can be seen from the amount of VAT paid and the VAT that should be paid. This research is based on the amount of VAT paid based on the policies set by the company, where VAT payments are the end result of the implementation of tax planning that has been determined by the previous company. The results of the analysis show that there is inefficiency in paying VAT. Inefficiency is the result of corporate tax management. Good tax management can be seen in the efficiency that the company can achieve.